Pengembangan Desain Lembaga Pendidikan Islam Dalam Lingkungan Keluarga: Sebuah Kajian Teoritis - Andri Irawan; Mauzifa Mauzifa (Al-Ahnaf: Journal of Islamic Education, Learning and Religious Studies, 2024)
The aim of writing this article is to examine the issue of the nature of Islamic Educational Institutions in the family. The family as the smallest unit in the educational institutional structure has all the roles and responsibilities in carrying out educational activities which we know as informal education. One of the problems that occurs in the implementation of family education, especially Islamic education, concerns the role and responsibility of parents as the main party in overseeing children's education. The research in this article uses library research with data collection techniques referring to various articles from journals, the internet and similar sources according to the topic of discussion, so that all the data referred to can be processed and analyzed theoretically in the hope of producing a clear and accountable reasoning construct. scientifically. The results of research through the study in this article can be concluded that the essence of Islamic Education Institutions in the family is that the home is the first place of school for children and that parents are the first teachers or educators in instilling the basic values of Islamic Education in children.